The Digital Change of Television in a Social Media Environment: The Case of the BBC - Zuell, Beatrice (Array, 2013)
The Internet has made new forms of participatory communication possible and has increased the amount of interpersonal communication, making possible countless ways for audiences and users to share, discuss, create and collaborate. This new participation of TV audiences in social media leads to an integration of TV consumption within the social media context. The broadcasters are challenged to develop new digital products and services to maintain the relationship with the viewer and to keep their attention, by building social interaction around the program and encouraging them to participate in social media platforms. The confrontation of television with growing social media platforms penetrates the TV world.